2014
DOI: 10.1038/nn.3689
|View full text |Cite
|
Sign up to set email alerts
|

Serial dependence in visual perception

Abstract: Visual input often arrives in a noisy and discontinuous stream, owing to head and eye movements, occlusion, lighting changes, and many other factors. Yet the physical world is generally stable—objects and physical characteristics rarely change spontaneously. How then does the human visual system capitalize on continuity in the physical environment over time? Here we show that visual perception is serially dependent, using both prior and present input to inform perception at the present moment. Using an orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

92
1,025
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 646 publications
(1,200 citation statements)
references
References 46 publications
92
1,025
19
Order By: Relevance
“…Similar attractive shifts have also been reported for items held serially (Fischer & Whitney, 2014;Huang & Sekuler, 2010) or simultaneously in visual working memory (Brady & Alvarez, 2011). For example, Brady and Alvarez had subjects remember the sizes of a set of circles; when subjects were asked to report the size of a single circle, their reports were biased toward the mean size of the set.…”
Section: Discussionsupporting
confidence: 75%
“…Similar attractive shifts have also been reported for items held serially (Fischer & Whitney, 2014;Huang & Sekuler, 2010) or simultaneously in visual working memory (Brady & Alvarez, 2011). For example, Brady and Alvarez had subjects remember the sizes of a set of circles; when subjects were asked to report the size of a single circle, their reports were biased toward the mean size of the set.…”
Section: Discussionsupporting
confidence: 75%
“…The mechanism by which the visual system accomplishes this object continuity remains elusive. Recent results have demonstrated that the perception of low-level stimulus features such as orientation and numerosity is systematically biased (i.e., pulled) toward visual input from the recent past [1, 2]. The spatial region over which current orientations are pulled by previous orientations is known as the continuity field, which is temporally tuned for the past 10–15 s [1].…”
mentioning
confidence: 99%
“…5B-D), priming for match pairs t(8) = 7, p = 0.0001; for mismatch pairs t(8) = 7.3, p < 0.0001; the difference in priming strength was not significant t(8) = 1.9, p = 0.09. Therefore, we conclude that although priming of perceptual states can stabilize perception Cicchini et al, 2014;Fischer & Whitney, 2014), prior knowledge about physical transformations is gathered in addition to and independent of it.…”
Section: Transformation Priming Cannot Be Explained By Priming Of Permentioning
confidence: 81%
“…For example, perceptual adaptation is thought to prioritize perceptual sensitivity (Kohn, 2007;Pastukhov, García-Rodríguez, et al, 2013;Theodoni, Kovács, Greenlee, & Deco, 2011;Webster, 2011). Conversely, neural persistence (Coltheart, 1980;Loftus & Irwin, 1998;Pastukhov & Braun, 2013b) and a rolling average over a longer period of perceptual history are thought to be used to minimize influence of neural noise and ensure perceptual constancy Cicchini et al, 2014;Fischer & Whitney, 2014). Finally, several mechanisms work as predictive memories trying to optimize target selection and processing (Chopin & Mamassian, 2012;Grill-Spector, Henson, & Martin, 2006;Kristjánsson & Campana, 2010;Maljkovic & Nakayama, 1994, 2000Schacter, Dobbins, & Schnyer, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation